A robust approach towards green synthesis of polyaniline-Scenedesmus biocomposite for wastewater treatment applications. (6th February 2019) - Maqbool, Munazza; Bhatti, Haq Nawaz; Sadaf, Sana; Zahid, Muhammad; Shahid, Muhammad
Abstract: The current study presents the synthesis of polyaniline- Scenedesmus biocomposite and its use as an efficient adsorbent for removal of contaminants from aqueous solutions. Initially, the Scenedesmus strain was cultivated in municipal wastewater. The Physico-chemical analysis of municipal wastewater after microalgae growth depicted 85.5% reduction in total nitrogen, 83.2% reduction in phosphorus and 89.3% reduction in chemical oxygen demand which clearly reveals that this strain can be efficiently used to avoid eutrophication caused by municipal wastewaters. The biomass of Scenedesmus strain obtained was harvested and de-oiled. The de-oiled biomass was further used for the adsorptive removal of Reactive red 120 (RR 120) from aqueous solutions. The biomass was treated with H2 SO4 and was used in three different forms; free, immobilized and polyaniline composite and all these three different forms of biomass showed adsorption potential of 713.02, 682.52 and 752.68 (mg g −1 ) respectively. Characterization of biomass was carried out by SEM, FT-IR and pHpzc determination. Kinetic study showed best fitness of pseudo second order kinetic model and experimental data was best fitted with Freundlich adsorption isotherm model. The study results indicated that this strain has good potential for adsorptive removal of contaminants from wastewaters.